The Effects of Technology Utilization in the Learning Process on Students' Psychological Well-being: The Perspectives of Constructivism Theory - Suhartono, Suhartono; Puspitoningrum, Encil; Pramono, Susatyo Adhi; Judijanto, Loso; Purnama, Dody Wahyudi (JETL (Journal of Education, Teaching and Learning), 2024)
This research aims to make a significant contribution to the understanding of constructivism in the context of education through an in-depth exploration of the use of technology in the learning process and its impact on the psychological well-being of students. The study employs a quantitative approach, utilizing structural equation modeling (SEM) and Partial Least Square (PLS) for analysis. The research participants consist of 100 university students in Malang, Indonesia, selected to complete an online questionnaire. The study results indicate that the integration of technology into the learning process has a positive and significant impact on students' psychological well-being. The application of constructivism theory as a conceptual foundation for understanding the influence of technology in learning demonstrates that students' interactive role in constructing knowledge has a substantial effect. The use of various platforms such as Google Drive, Google Docs, Microsoft Office, Zoom, Google Meet, Canvas, Moodle, Grammarly, and Mendeley creates a learning context that facilitates collaboration, active participation, and the development of students' social skills. In the context of students' mental well-being, technology helps alleviate burdens by providing flexibility in completing tasks, stimulating a sense of connection through collaboration, and offering psychological support.